The Pest Severity, Insecticide Application, and Land Use Data for 51 Counties in China, 1991-2015 - International Food Policy Research Institute; Chinese Academy of Agricultural Sciences; Ministry of Agriculture and Rural Affairs, Government of China; Chinese Academy of Sciences (International Food Policy Research Institute, 2018)
This is a compiled unique long-term panel dataset that consists of data on (i) pest severity and insecticide applications per annum per county by pest species, and (ii) land cover/use data. The counties in the database are the 51 most important cotton-growing counties, by production, in the Yangtze River valley and Yellow River valley cotton production regions, while the data covered the years 1991–2015, with complete coverage of counties in all years when cotton was cultivated. Between 2011 and 2013, eight counties in our sample stopped cultivating cotton. The number increased to 11 and 12 counties in 2014 and 2015, respectively, resulting in 47 missing records. The national cotton pests monitoring network, maintained by the Ministry of Agriculture mandates the main cotton-producing counties to collect yearly data on pest infestation levels and insecticide applications for key cotton pests following national standardized monitoring and categorization methods. Tailored scouting methods were used for different pests. In each county, 10–20 fields were selected for pest monitoring in each year. Insect populations were recorded every 3–10 days from early June to late August each year, and the seasonal average abundance across the surveyed fields were used for scoring using a five-point scale of levels I–V. Data on the number of insecticide applications targeted at specific pests were collected by interviewing farmers at each scouting to estimate yearly pest-specific total number of sprays for each county. While the detailed data collection methods and protocols should inspire confidence in the data, the reliability of the pest level data depends on the accuracy, knowledge, and honesty of the respondents, as is the case with any non–first-hand data. County-level land use data were drawn from a national land cover/use database developed by the Chinese Academy of Sciences, using satellite remote-sensing data from the Landsat Thematic Mapper/Enhanced Thematic Mapper images. The database offers the most comprehensive coverage of China’s land use/cover and has been used in a number of published studies. The land use data for 6 years (1990-2015) at 5 years interval were extracted. The proportional area for each six main land use classes as well as the Shannon index for land use diversity for each county for six years was computed. Land use proportions in the intermediate years (e.g., 1991, 1992, 1993, 1994, 1996, etc.) were calculated by linear interpolation between the data.